2021
DOI: 10.1038/s41598-020-80724-0
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methotrexate-based regimens and post-remission consolidation for treatment of newly diagnosed primary CNS lymphoma: meta-analysis of clinical trials

Abstract: With the exception of high-dose methotrexate (HD-MTX), there is currently no defined standard treatment for newly diagnosed primary central nervous system lymphoma (PCNSL). This review focused on first-line induction and consolidation treatment of PCNSL and aimed to determine the optimal combination of HD-MTX and the long-term beneficial consolidation methods. A comprehensive literature search of MEDLINE identified 1407 studies, among which 31 studies met the inclusion criteria. The meta-analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Only marginally better are conventional DLBCL regimes with response rates ranging from 19 to 59% and less than half patients surviving at two years from diagnosis [2,3]. A significant improvement in prognosis comes from modern multidrug regimens incorporating high-dose methotrexate (HD-MTX) with appropriate consolidation (2 years OS of 80% and a five-year OS of 77%) [47]. More recent regimes utilizing autologous stem cell transplantation as consolidation report twoyear OS as high as 81% [48].…”
Section: Evolution Of Treatment Modalitiesmentioning
confidence: 99%
“…Only marginally better are conventional DLBCL regimes with response rates ranging from 19 to 59% and less than half patients surviving at two years from diagnosis [2,3]. A significant improvement in prognosis comes from modern multidrug regimens incorporating high-dose methotrexate (HD-MTX) with appropriate consolidation (2 years OS of 80% and a five-year OS of 77%) [47]. More recent regimes utilizing autologous stem cell transplantation as consolidation report twoyear OS as high as 81% [48].…”
Section: Evolution Of Treatment Modalitiesmentioning
confidence: 99%
“…Combination of HD‐MTX with other cytostatic agents provides best clinical results, when feasible. Two meta‐analyses have demonstrated HD‐MTX in combination with other agents (particularly cytarabine) is associated with highest response rates and improved survival outcomes 51 . The use of rituximab in PCNSL has been a matter of recent controversy; the phase 3 Hovon 105/ALLG‐NHL‐24 trial found no benefit of rituximab addition to the MTX/carmustune/teniposide/prednisone combination (MBVP).…”
Section: Treatment Of Pcnsl In the Elderlymentioning
confidence: 99%
“…Generally, PCNSL has a cure rate below 40% with MTX-based regimens and is subject to late recurrences (1,(29)(30)(31)(32). In their analysis of 31 studies published between 1992 and 2019, Yu et al have reported that PCNSL patients achieved a pooled CRR of 41% across all HD-MTX-based regimens (33). Additionally, three-and four-drug regimens achieved better CRRs than HD-MTX monotherapy (33).…”
Section: Treatment Methotrexate-based Chemotherapymentioning
confidence: 99%